Low-molecular-weight heparin therapy reduces 28-day mortality in patients with sepsis-3 by improving inflammation and coagulopathy - Zhang, Ze; Yan, Taotao; Ren, Danfeng; Zhou, Jingwen; Liu, Liangru; Li, Juan; Fu, Shan; Ni, Tianzhi; Xu, Weicheng; Yang, Yuan; Chen, Tianyan; He, Yingli; et al. (Frontiers in Medicine, 2023)
Sepsis is a syndromic response to infection with high-mortality, causing a significant global burden of disease. Although low-molecular-weight heparin (LMWH) has been recommended to prevent venous thromboembolism, its anticoagulant and anti-inflammatory effects in sepsis remain controversial. With the update of Sepsis-3 definition and diagnostic criteria, the efficacy and benefit population of LMWH need to be further evaluated. We performed a retrospective cohort study to assess whether LMWH improved the inflammation, coagulopathy, and clinical outcomes against Sepsis-3 and to identify the optimal patients. All patients diagnosed with sepsis at the largest general hospital in northwest China from January 2016 to December 2020 were recruited and re-evaluated using Sepsis-3 criteria. After 1:1 propensity scoring matching, 88 pairs of patients were categorized into the treatment and control group based on subcutaneous LMWH administration. Compared with the control group, a significantly lower 28-day mortality was observed in LMWH group (26.1% vs. 42.0%, p = 0.026) with comparable incidence of major bleeding events (6.8% vs. 8.0%, p = 0.773). Cox regression analysis showed LMWH administration was the independent protective factor for septic patients (aHR, 0.48; 95% CI, 0.29 to 0.81; p = 0.006). Correspondingly, the LMWH treatment group showed evident improvement in inflammation and coagulopathy. With further subgroup analysis, LMWH therapy was found to be associated with favorable outcomes in patients younger than 60 years old, with sepsis-induced coagulopathy (SIC), ISTH overt DIC, non-septic shock, non-diabetic, and moderate-risk group (APACHE II score 20 to 35, or SOFA score 8-12, respectively). Collectively, our data show that LMWH improves 28-day mortality by improving inflammatory response and coagulopathy in patients meeting Sepsis-3 criteria. The SIC and ISTH overt DIC scoring systems can better identify septic patients benefiting more from LMWH administration.